Diet and niche breadth and overlap in fish communities within the area affected by an Amazonian reservoir (Amapá, Brazil) - OLIVEIRA, Júlio Cesár Sá de (2015)
We investigated the niche breadth and overlap of the fish species occurring in four environments affected by the Coaracy Nunes reservoir, in the Amapá Brazilian State. Seasonal samples of fishes were taken using a standard configuration of gillnets, as well as dragnets, lines, and cast¬nets. Five hundred and forty stomach contents, representing 47 fish species were analyzed and quantified. Niche breadth and overlap were estimated using indexes of Levins and Pianka, respectively, while interspecific competition was evaluated using a null model (RA3). ANOVA and the Kruskal¬Wallis test were used, respectively, to evaluate differences in niche breadth and overlap between areas. The data indicate that the majority of the fish species belong to the piscivore, omnivore, and detritivore guilds. These species have likely colonized the environments due to the availability of suitable feeding resources, and the favorable physical conditions created by the river damming. Overall, few species have ample niches, but most of them are highly specialized. Resources seasonal variation had little effect on the feeding behavior of most species in the study areas. The null models indicated that competition was not a factor determining on community structure.